Robotic Digitalization and Business Success: The Central Role of Trust and Leadership in Operational Efficiency—A Hybrid Approach Using PLS-SEM and fsQCA - Miguel Gonzalez-Mohino; Mario J. Donate; Guzman A. Munoz-Fernandez; L. Javier Cabeza-Ramirez (IEEE Access)
While digitalization and robotics are a reality for companies and contribute to value creation, few studies have examined their impact on operational performance. This study examines how digitalization (with robots and artificial intelligence-AI) in companies contributes to improving operational performance, emphasizing the importance of trust and effective knowledge-oriented leadership to create a positive context for its implementation. The research included ten companies, where an engineer in a managerial position was surveyed to obtain a strategic perspective, complemented by responses from 108 employees to reflect the operational perspective. Through qualitative comparative analysis with fuzzy sets (fsQCA) and Partial Least Squares Structural Equation Modeling (PLS-SEM), combinations of factors leading to business success from the perspective of digitalization are identified. Findings reveal that trust in robots and AI and effective leadership are crucial for improving operational efficiency in an increasingly digitized business environment. This study provides valuable insights into how the integration of advanced digital technologies through organizational factors such as knowledge-oriented leadership can contribute to improved operational performance, offering practical perspectives to managers on how to handle digitalization in organizations.